Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Problem Based Learning di Kelas IV Sekolah Dasar - Rahmadevi, Triska; S, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This study aims to describe the increase in student learning results on thematic Integrated Learning Model using Problem Based Learning in class IV SDN 14 Gadut Kabupaten Agam. This research used a qualitative and quantitative approach. This type of research i.e. Research Action class (PTK). The subject of research is the grade IV SDN 03 Labuah Bukittinggi Feed as many as 16 students. Research conducted two cycles. The design of the research include, (1) planning, (2) implementation, (3) and (4) observation of the reflection. The results showed an increase in: a) the RPP cycle I 85.93% Cycle II (B) 93,75% (SB) b) implementation on aspect of teacher cycle I 85.71% (B), a cycle II 96,42% (SB) c) Implementation on aspect students cycle I 85.71% (B) and Cycle II 96,42% (SB) d) student learning outcomes s iklus I 74,5 Cycle (B), II (B) 84,84. Thus the model of Problem Based Learning can improve the learning results of integrated thematic grade IV SDN 14 Gadut Kabupaten Agam.